Finding a STAR in a Vehicular Cloud - Mershad, Khaleel (2013)
The strong capabilities that exist in a Vehicular Ad hoc Network (VANET) has given birth to the concept of Vehicular Clouds, in which cloud computing services are hosted by vehicles that have sufficient resources to act as mobile cloud servers. In this paper, we design a system that enables vehicles in a VANET to search for mobile cloud servers that are moving nearby and discover their services and resources. The system depends on RSUs that act as cloud directories with which mobile cloud servers register. The RSUs share their registration data to enable vehicles to discover and consume the services of mobile cloud servers within a certain area. We evaluated the proposed system using the ns2 software and demonstrated through comparing the results to another mechanism the feasibility and efficiency of our system in terms of service discovery and service consuming delays and packet success ratio.